Burden of Systolic and Diastolic Left Ventricular Dysfunction Among Hispanics in the United States: Insights From the Echocardiographic Study of Latinos. (April 2016) - Mehta, Hardik; Armstrong, Anderson; Swett, Katrina; Shah, Sanjiv J.; Allison, Matthew A.; Hurwitz, Barry; Bangdiwala, Shrikant; Dadhania, Rupal; Kitzman, Dalane W.; Arguelles, William; Lima, Joao; Youngblood, Marston; et al.
Abstract : Background—: Population-based estimates of cardiac dysfunction and clinical heart failure (HF) remain undefined among Hispanics/Latino adults. Methods and Results—: Participants of Hispanic/Latino origin across the United States aged 45 to 74 years were enrolled into the Echocardiographic Study of Latinos (ECHO-SOL) and underwent a comprehensive echocardiography examination to define left ventricular systolic dysfunction (LVSD) and left ventricular diastolic dysfunction (LVDD). Clinical HF was defined according to self-report, and those with cardiac dysfunction but without clinical HF were characterized as having subclinical or unrecognized cardiac dysfunction. Of 1818 ECHO-SOL participants (mean age 56.4 years; 42.6% male), 49.7% had LVSD or LVDD or both. LVSD prevalence was 3.6%, whereas LVDD was detected in 50.3%. Participants with LVSD were more likely to be males and current smokers (all P <0.05). Female sex, hypertension, diabetes mellitus, higher body mass index, and renal dysfunction were more common among those with LVDD (all P <0.05). In age–sex adjusted models, individuals of Central American and Cuban backgrounds were almost 2-fold more likely to have LVDD compared with those of Mexican backgrounds. Prevalence of clinical HF with LVSD (HF with reduced EF) was 7.3%; prevalence of clinical HF with LVDD (HF with preserved EF) was 3.6%. 96.1% of the cardiac dysfunction seen was subclinical or unrecognized. Compared with those with clinical cardiac dysfunction, prevalent coronary heart disease was the only factor independently associated with subclinical or unrecognized cardiac dysfunction (odds ratio: 0.1; 95% confidence interval: 0.1–0.4). Conclusions—: Among Hispanics/Latinos, most cardiac dysfunction is subclinical or unrecognized, with a high prevalence of diastolic dysfunction. This identifies a high-risk population for the development of clinical HF.